The Influence of Physical Therapy Guideline Adherence on Healthcare Utilization and Costs among Patients with Low Back Pain: A Systematic Review of the Literature. - William J Hanney; Michael Masaracchio; Xinliang Liu; Morey J Kolber (PLoS ONE)
Background Low back pain (LBP) is common and associated healthcare costs are significant. While clinical practice guidelines have been established in an attempt to reduce costs and healthcare utilization, it is unclear if adherence to physical therapy guidelines for those with LBP is efficacious. Therefore, the purpose of this study was to assess current evidence and evaluate the impact of physical therapy guideline adherence on subsequent healthcare costs and utilization for patients with LBP. Methods An electronic search was conducted in PubMed, CINAHL (EBSCO Host), AMED (Ovid), and PEDro. Studies included in this review were published in peer reviewed journals and the primary mode of treatment was administered by a physical therapist. Also, the definition of adherence was clearly defined based on claims data and at least one measure of cost or utilization reported. Quality assessment was evaluated via a modified Downs and Black checklist. Due to the conceptual heterogeneity in variable measurements, data were qualitatively synthesized and stratified by reported utilization and cost measures. Results A total of 256 results were identified and after omitting duplicates, 4 articles were retained, which were all retrospective in nature. Quality scores ranged between 19 and 21 points out of a possible 26 on the modified Downs and Black checklist. All identified studies used the same definition of guideline adherence, which focused on billing active codes and minimizing use of passive codes. The results demonstrated trends that, with a few exceptions, suggested those patients with LBP that were treated with an adherent guideline program demonstrated decreased healthcare utilization and an overall healthcare savings. Conclusion Preliminary evidence suggests that adherence to established clinical practice guidelines may assist with decreasing healthcare utilization and costs. Additional research based on prospective randomized controlled trials are needed to provide high quality evidence regarding the impact of guideline adherence among patients with LBP.